Immunosuppressive treatment in fulminant myocarditis and gene expression pattern associated with, but no histological confirmation of giant cell myocarditis. (31st January 2017) - Fruhwald, Friedrich; Lassner, Dirk; Fruhwald, Sonja; Gross, Ulrich M.; Dapunt, Otto; Schultheiss, Heinz‐Peter
Abstract: A healthy woman with acute onset of pulmonary oedema and severely depressed left ventricular function underwent endomyocardial biopsy under the clinical suspicion of fulminant myocarditis. While awaiting the results of biopsy, the situation deteriorated to Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) and extracorporeal membrane oxygenation was implanted. Finally, immunohistochemistry in biopsy specimen corresponded to fulminant lymphocytic myocarditis, although active myocarditis was excluded. Furthermore, gene expression profiling identified giant cell myocarditis although multinuclear cells were absent. This prompted the start of immunosuppression with cortisone and cyclosporine. The patient fully recovered.